Long Noncoding RNAs in Yeast Cells and Differentiated Subpopulations of Yeast Colonies and Biofilms. (25th March 2018) - Wilkinson, Derek; Váchová, Libuše; Hlaváček, Otakar; Maršíková, Jana; Gilfillan, Gregor D.; Palková, Zdena
Abstract : We summarize current knowledge regarding regulatory functions of long noncoding RNAs (lncRNAs) in yeast, with emphasis on lncRNAs identified recently in yeast colonies and biofilms. Potential regulatory functions of these lncRNAs in differentiated cells of domesticated colonies adapted to plentiful conditions versus yeast colony biofilms are discussed. We show that specific cell types differ in their complements of lncRNA, that this complement changes over time in differentiating upper cells, and that these lncRNAs target diverse functional categories of genes in different cell subpopulations and specific colony types.